(untitled) (Biological Sciences - PJSIR, 1997)
Abundanceofgreenleafhoppers,Nephotettix sp.andinterrelationshipbetweengreenleafhoppersandtheirnatural predatorswasstudiedon21ricevarieties/lines. ThevarietyKladomaandlineBG-915showedminimumandmaximum susceptibilityto greenleafhopperattack.The highestleafhopperpopulationwasrecorded35days aftertransplanting andthereafteragradualdensitydeclineonplantageoccured.Outoffivepredatorsnamely,Conocephalus, Tetragnatha, .Micraspis, Oxyopes andAgriocnemus, predatorMicraspis is themost importantwhich madehighlypositivecorrela- tion(0.1’69),maximumdirecteffects(0.144)andmaximuminfluences(2.85%)ontheabundanceofgreenleafhoppers,